Power-Constrained Image Enhancement Using Multiband Processing for TFT LCD Devices With an Edge LED Backlight Unit - Choi, Dong Yoon; Song, Byung Cheol (IEEE transactions on circuits and systems for video technology, 2018)
This paper presents a subband-decomposed image-enhancement algorithm that can preserve the luminance and contrast levels in power-controllable thin-film-transistor liquid-crystal display devices. The proposed algorithm consists of three steps. First, an input image is decomposed to multiscale subbands via subband decomposition. Second, luminance compensation and contrast preservation are achieved simultaneously by adjusting the gain of each subband properly. Third, additional power consumption caused by excessive boosting, while coping with the local dimming through specific clipping, is prevented. The experimental results show that the proposed algorithm provides more natural details and contrast, while preserving more similarities with the original, than the existing methods. Even in terms of the peak signal-to-noise-ratio and the structural similarity index, the proposed algorithm has 27.8% and 3.8% higher values compared to a state-of-the-art method. The real-time operation of the proposed algorithm was verified through intensive optimization and the Compute Unified Device Architecture implementation. In addition, the power-reduction effect of the proposed algorithm on commercial monitors was investigated experimentally.